2016
DOI: 10.1016/j.schres.2016.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime suicide intent, executive function and insight in schizophrenia and schizoaffective disorders

Abstract: Objectives Lack of insight and neurocognitive deficits are often seen in schizophrenia patients. While there are several studies investigating the relationship between suicidal ideation, executive function and insight, there are relatively fewer investigating the triangular relationship between suicide intent, insight and cognitive competence in schizophrenia. The aim of our study was to address this issue. Methods One hundred seventy five subjects with DSM-IV TR diagnoses of schizophrenia or schizoaffective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 33 publications
(41 reference statements)
3
22
1
Order By: Relevance
“…It has been suggested that other contributing factors, such as neurocognitive functioning, may be more sensitive in the prediction of SB [7] than the classic risk factors. Indeed, some previous studies suggested that the presence of SB was associated with better neurocognitive performance in domains such as executive functioning [8][9][10]. In keeping with this, the aforementioned study we found significant differences in processing speed functioning at baseline between patients with SB and those without SB prior to first contact with services [5].…”
Section: Introductionsupporting
confidence: 90%
“…It has been suggested that other contributing factors, such as neurocognitive functioning, may be more sensitive in the prediction of SB [7] than the classic risk factors. Indeed, some previous studies suggested that the presence of SB was associated with better neurocognitive performance in domains such as executive functioning [8][9][10]. In keeping with this, the aforementioned study we found significant differences in processing speed functioning at baseline between patients with SB and those without SB prior to first contact with services [5].…”
Section: Introductionsupporting
confidence: 90%
“…None of these studies found a difference in cognitive performance between SCZ patients with or without a history of suicide attempts. However, studies have found both negative and positive relationships between cognitive performance and suicide risk, 8,36 which could be due to several reasons. Suicide attempters may have different neurocognitive characteristics than non-attempters, which suggests that comprehensive neurocognitive assessments are needed to investigate their relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Studies and observations suggest that the following demographic and psychosocial factors increase the risk of suicide in individuals with schizophrenia [10,29,33,34,35,36]:Younger ageBeing maleBeing unmarriedLiving aloneBeing unemployedBeing intelligentBeing well-educatedGood premorbid adjustment or functioningHaving high personal expectations and hopesHaving an understanding that life’s expectations and hopes are not likely to be metHaving had recent (i.e., within past 3 months) life eventsHaving poor work functioningHaving access to lethal means, such as firearms…”
Section: Demographic and Psychosocial Risk Factorsmentioning
confidence: 99%